Contrastive Performance Analysis of US-OIDMA using Different Code Rate and Constraint Length - Ajay Kumar Maurya, Ravi Prakash, Rakesh Kumar Maurya, B. B.Tiwari; R. K. Singh (International Journal of Advanced Science and Technology, 2020)
The performance analysis of US-OIDMA with convolutional codes of different code rate and constraint lengths are mainly discussed in this research paper. The special type of CDMA is known as IDMA and its technology is based on interleaving mechanism. When optical channels are used in IDMA it’s named as OIDMA. In US-OIDMA concept spreading of all users are done along with user-specific interleavers. Actually the US-OIDMA is the combination of OCDMA and OIDMA and it provide the better performance with low loss. Every digital communication system the coding is a prime constraint. The convolutional codes are used for burst error correction in noisy communicational channel. I have used convolutional codes of different code rates and constraints lengths in coding section of US-OIDMA system. The whole US-OIDMA system is programmed on MATLAB. Performance analysis of US-OIDMA in terms of BER is observed. For analysis purpose random interleaver with minimum optical loss window 1330nm is used.